Global-scale seasonally resolved black carbon vertical profiles over the Pacific - Schwarz, J; Samset, B; Perring, A; Spackman, JR; Gao, R; Stier, P; Schulz, M; Moore, F; Ray, E; Fahey, D (John Wiley and Sons, 2013)
Black carbon (BC) aerosol loadings were measured during the High-performance Instrumented Airborne Platform for Environmental Research Pole-to-Pole Observations (HIPPO) campaign above the remote Pacific from 85°N to 67°S. Over 700 vertical profiles extending from near the surface to max ∼14 km altitude were obtained with a single-particle soot photometer between early 2009 and mid-2011. The data provides a climatology of BC in the remote regions that reveals gradients of BC concentration reflecting global-scale transport and removal of pollution. BC is identified as a sensitive tracer of extratropical mixing into the lower tropical tropopause layer and trends toward surprisingly uniform loadings in the lower stratosphere of ∼1 ng/kg. The climatology is compared to predictions from the AeroCom global model intercomparison initiative. The AeroCom model suite overestimates loads in the upper troposphere/lower stratosphere (∼10×) more severely than at lower altitudes (∼3×), with bias roughly independent of season or geographic location; these results indicate that it overestimates BC lifetime. Key Points A BC climatology is provided for the remote Pacific and Polar regions AeroCom overestimates remote BC with strong altitude dependence Extratropical mixing into the TTL is estimated from BC latitudinal gradients ©2013 The Authors. Geophysical Research Letters published by Wiley on behalf of the American Geophysical Union.